Benign tumors of the vulva - Samamé Boggio, Guido (2015)
There have been five cases of "benign tumors of the vulva"; these tumors were all located in the labia majora, with few symptoms and whose age varies between 24 and 54 years, its development time was 6 months to 9 years. Tumor size varies from one lemon to the head of a fetus, the clinical diagnosis agreed on most of the time with the pathological results.